2020
DOI: 10.1371/journal.pbio.3000808
|View full text |Cite
|
Sign up to set email alerts
|

Klf5 down-regulation induces vascular senescence through eIF5a depletion and mitochondrial fission

Abstract: Although dysregulation of mitochondrial dynamics has been linked to cellular senescence, which contributes to advanced age-related disorders, it is unclear how Krü ppel-like factor 5 (Klf5), an essential transcriptional factor of cardiovascular remodeling, mediates the link between mitochondrial dynamics and vascular smooth muscle cell (VSMC) senescence. Here, we show that Klf5 down-regulation in VSMCs is correlated with rupture of abdominal aortic aneurysm (AAA), an age-related vascular disease. Mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…55 Recently, a study showed that negative regulation of eIF5A induced by Klf5 knockdown, resulted in mitochondrial fission, demonstrating that eIF5a can act in the regulation of mitochondrial dynamics. 56 Here, we described for the first time the eIF5A isoform A functions regarding mitochondrial metabolism. Initially, cell activity was measured by MTT conversion in formazan through the action of NAD(P)H-dependent oxidoreductase enzymes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…55 Recently, a study showed that negative regulation of eIF5A induced by Klf5 knockdown, resulted in mitochondrial fission, demonstrating that eIF5a can act in the regulation of mitochondrial dynamics. 56 Here, we described for the first time the eIF5A isoform A functions regarding mitochondrial metabolism. Initially, cell activity was measured by MTT conversion in formazan through the action of NAD(P)H-dependent oxidoreductase enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…This effect was reported as a consequence of the negative regulation of mitochondrial complexes induced by eIF5A hypusination inhibition 55 . Recently, a study showed that negative regulation of eIF5A induced by Klf5 knockdown, resulted in mitochondrial fission, demonstrating that eIF5a can act in the regulation of mitochondrial dynamics 56 …”
Section: Discussionmentioning
confidence: 94%
“…When overexpressed, this longer isoform co-purifies with mitochondria [ 26 ]. Secondly, there is evidence for the role of eIF5A in preserving mitochondrial morphology, distribution and integrity, obtained in Schizosaccharomyces pombe and mammals [ 27 , 28 ]. Thirdly, the connection between eIF5A and mitochondria-mediated apoptosis has been described, where eIF5A overexpression in human cells increased reactive oxygen species (ROS) and yielded loss of the mitochondrial transmembrane potential, and the release of cytochrome-c and caspase activation [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same study the authors reported that over‐expression of eIF5A1 induced activation of caspase-3, -8, and -9 together with a loss of the mitochondrial transmembrane potential, release of cytochrome c , and translocation of Bax. Analysing the mitochondrial dynamics linked to cellular senescence Ma et al [ 86 ] reported that the Kruppel like factor 5 (KLF5 an essential transcriptional factor of cardiovascular remodeling, that mediates the link between mitochondrial dynamics and vascular smooth muscle cell senescence) knockdown enhanced, while KLF5 over-expression suppressed mitochondrial fission. Mechanistically, KLF5 activates eIF5A transcription through binding to its promoter, which in turn preserves mitochondrial integrity by interacting with mitofusin 1 (Mfn1).…”
Section: Apoptosis and Mitochondriamentioning
confidence: 99%